ADIPONECTIN LEVELS IN PATIENTS WITH CHRONIC KIDNEY DISEASE AND EXCESS BODY WEIGHT: RELATIONSHIP WITH METABOLIC PARAMETERS - Amonov Mukhammad Komil ugli (Modern American Journals, 2025)
The article presents the results of an experimental study aimed at examining adiponectin levels in patients with chronic kidney disease (CKD) and excess body weight, as well as their relationship with metabolic parameters. A negative correlation was found between serum adiponectin concentration and body mass index (BMI), triglyceride levels, and CKD stage. These data highlight the role of adiponectin as a potential marker of metabolic disorders in this patient population.